Outcomes and complications of patients undergoing Salter's innominate osteotomies for hip dysplasia: a systematic review of comparative studies. Issue 4 (19th March 2021) - Tejpal, Tushar; Shanmugaraj, Ajaykumar; Gupta, Arnav; Horner, Nolan S; Simunovic, Nicole; Kishta, Waleed; Ayeni, Olufemi R
Abstract: The purpose of this systematic review is to assess outcomes and complications of patients undergoing Salter's innominate osteotomies (SIOs) for the correction of hip dysplasia along with patient and technical factors that can be optimized to improve outcomes after SIO. MEDLINE and EMBASE were searched from data inception to 9 October 2018. Data were presented descriptively. Twenty-seven studies were identified including 1818 hips (87.1%) treated with SIO (mean age of 2.1 ± 2.5 years and mean follow-up of 3.5 ± 5.0 years). Patients undergoing SIO had a post-operative center-edge angle (CEA) of 31.3° ± 5.3° and an acetabular index (AI) angle of 16.1° ± 5.2°. Patients undergoing SIO with pre-operative traction had significantly lower ( P = 0.049) post-operative McKay criteria scores compared to patients without pre-operative traction. Patients undergoing SIO between the ages of 1.5–2 years had significantly better ( P < 0.05) post-operative McKay criteria scores compared to patients aged 4–6 years. The complication rate was 9.4% with avascular necrosis (2.5%) being most common. This review found that SIO for developmental dysplasia of the hip produces generally good post-operative clinical outcomes. The CEA and AI can be corrected to normal range after SIO. Patients may have superior outcomes if they have SIO at a younger age, were not treated with pre-operative traction and did not have untreated contralateral hip dysplasia. Outcomes appear to be similar between one-stage bilateral SIO and a two-stage procedure in the setting of bilateral hip dysplasia; however, more multicentered studies are needed to confirm these results.